TINGKAT PENGETAHUAN DAN SIKAP ORANG TUA YANG MEMILIKI ANAK AUTIS TENTANG TUMBUH KEMBANG ANAK AUTIS DI KLINIK FADIRA BINJAI TAHUN 2018 - Nurhafni Nurhafni (COLOSTRUM JURNAL KEBIDANAN, 2020)
Growth is increasing in size and the cell size of all parts of the body, development is increasing body structure and function that is more complex in the ability to coarse motion, smooth motion, speech and language and socialization and independence. Autism is a neurobiological development disorder that is very complex / long in life, which includes disturbances in aspects of social interaction, communication and language, and behavior and emotional disturbances and sensory perceptions even in the motor aspects. Autistic symptoms appear before 3 years of age. Knowledge is the result of "knowing" and this occurs after people have sensed a particular object. Attitude is the most important concept in social psychology that addresses the elements of attitudes both as individuals and groups. The type of research used in this research is descriptive method. This research was conducted at the Fadira Binjai clinic. Data collection is taken using primary data. With a sample of all the total population (total sampling) all parents who have autistic children in the fadira Binjai clinic. The results showed that there were 17 parents (56.67%) with good knowledge of autistic children and 5 (16.66%) good knowledge. Parents who have autistic children have a positive attitude of 17 people (56.67%) and have a negative attitude of 13 people (43.33%). From the results of the above research, it is expected that parents who have autistic children in order to increase their understanding of autism and the development of autistic children can through group discussions with a nurse doctor or midwife, friends to find out information through magazine and television books.